(untitled) (SAARC Journal of Agriculture, 2026)
Potato (Solanum tuberosum) is one of the most important staple crops worldwide and understanding the genetic diversity is critical for breeding improved varieties with desirable traits. In Bangladesh, the Bangladesh Agricultural Research Institute (BARI) has released numerous potato varieties; however, molecular-level insights into their genetic diversity remain scarce. This study aimed to evaluate the genetic diversity of 36 BARI-released potato varieties using simple sequence repeat (SSR) markers to identify genetically divergent genotypes for breeding and improvement programs. The study conducted from October 2020 to November 2022 at the Institute of Biotechnology and Genetic Engineering (IBGE) and the Advanced Plant Breeding Laboratory, Gazipur Agricultural University (GAU), nine SSR primers (STM 1049, STM 2022, STM 2013, STM 1104, STM 1106, STM 0037, STM 0030, STM 0019, and STM 1031) were employed. A total of 10.56 alleles per locus were detected, with STM 0030 producing the highest number of alleles (13) and STM 1104 the least (6). The polymorphic information content (PIC) values ranged from 0.44 (STM 1104) to 0.90 (STM 2013 and STM 0030), indicating the high discriminatory power of these markers. Genetic distance analysis revealed significant diversity, with the highest inter-genotypic distance observed between BA-40 and BA-46 (0.8571) and the lowest between BA-91 and BA-41 (0.33). These results demonstrate the effectiveness of SSR markers, particularly STM 2013 and STM 0030, in differentiating potato genotypes. The findings provide critical insights for designing breeding strategies and highlight the potential for leveraging genetic diversity to develop resilient and high-yielding potato varieties. SAARC J. Agric., 23(2): 145-158 (2025)